Urban-Rural Differences in Indoor and Outdoor Air Quality: A Comparative Study in Bangladesh - Masamitsu Kurata; Akira Hibiki; Kazushi Takahashi; Yutaka Matsumi (Toxics, 2025)
Health hazards caused by indoor air pollution (IAP) remain a global concern, especially in developing countries. IAP has complex mechanisms related to outdoor air pollution (OAP) and various other factors, and their relationship needs to be clarified to examine effective policies. We conducted an indoor and outdoor air monitoring survey in urban, peri-urban, and rural areas in Bangladesh, one of the countries with the most severe air pollution. The results show that IAP is more severe in urban households than in rural households, with a five-fold difference in daily indoor <semantics>PM2.5</semantics> concentration between 117 <semantics>μg/m3</semantics> and 22 <semantics>μg/m3</semantics>, respectively. Regression analysis reveals that IAP is strongly associated with OAP and is hardly affected by solid fuels used in well-ventilated outside kitchens. Our findings support the view that the mitigation of IAP in developing countries can be achieved not only through a transition to clean fuels, which often entails substantial costs, but also through more practical and accessible alternatives, such as the use of outdoor kitchens, electric fans, and careful management of behaviors such as indoor smoking and mosquito coil use.